Designing a business model from process perspective - (:unkn) unknown (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2019)
The business model is a relatively new concept in entrepreneurship and strategic management literature. Thus, the growing body of business model literature contains qualitative research, especially case studies. The key reason business models are explained via case studies is that the business model concept is recorded in the literature from successful firms' business model practices to business model theory and, as a result, different theories arise accordingly. Following the previous implications, the purpose of this article is to demonstrate how business models are developed and implemented. A case study of Istanbul Metropolitan Municipality's transportation strategy and implementation of a business model has been conducted in detail, followed by an explanation of the concept. To focus on the maritime industry and bridge the gap in Turkey's water transportation, a business model development process for the water transportation industry was proposed and then applied to all industries. The evaluation of the business model concept from a process perspective led us to achieve a generalized model, indicating how a successful business model can be implemented by other firms. As a result, we found that a successful business model must be valuable, profitable and sustainable. In addition, a successful business model greatly contributes to the sustainability of any firm and offers a novel framework to firms which desire to get a competitive advantage.
Keywords: business model; business model development process; business model implementation process; strategy; water transportation; FUTURE; VIEW